Values informing the development of an indicator of appropriate diabetes therapy: qualitative study - Víctor M Montori; Nilay D Shah; Rozalina G McCoy; Christina M LaVecchia (BMJ Open)
Objectives Despite increasing focus on individualised diabetes management, current diabetes quality measures are based on meeting generic haemoglobin A1c thresholds and do not reflect considerations of clinical complexity, hypoglycaemic susceptibility or treatment burden. Our team observed a multidisciplinary stakeholder panel tasked with informing an appropriate diabetes therapy indicator (ADTI) and analysed their deliberations, seeking to understand what constitutes appropriate diabetes therapy and how it can be captured using an operational quality indicator. We focused specifically on factors the panel valued in an ideal indicator, how they defined appropriateness and how they thought an indicator of appropriateness could be operationalised.Design Qualitative study examining Delphi panel deliberations as it iteratively refined the ADTI.Participants and methods The 12-member panel was comprised of clinicians (endocrinology, primary care, geriatrics), pharmacists, nurses, researchers, and representatives of public and private health plans. It met for four teleconference calls and deliberated asynchronously using semi-structured questionnaires following each call to develop the ADTI. These semistructured questionnaires, as well as the meeting minutes, were then analysed using an inductive thematic approach.Results We identified three themes in panellist discussions that represented the core value systems underpinning the indicator and its formation: (1) promoting individualised, evidence-based and equitable care; (2) balancing autonomy and prescriptiveness in clinical decision-making; and (3) ensuring an accurate, reliable and practical indicator. These three principles were operationalised into definitions of treatment intensity and clinical complexity, and yielded an indicator that participants judged both fair and effective.Conclusions Better understanding of what multidisciplinary stakeholders perceive as appropriate diabetes management can help develop quality indicators that are patient-centred, evidence-based, equitable and pragmatic across a range of clinical settings.